Social Emotional Learning to Improve Collaboration and Questioning Skills in Elementary Schools - Budiansyah; Laihat, Laihat; Rantina, Mahyumi (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2025)
This study investigates the impact of social-emotional learning (SEL) on enhancing collaboration and questioning skills in elementary school students. The research focuses explicitly on 31 first-grade students in Palembang. Employing a classroom action research methodology, the study is structured into two cycles, each comprising planning, implementation, observation, and reflection stages. Data collection involved both observational techniques and testing. The results indicate marked improvements in collaboration and questioning skills across three phases: pre-cycle, cycle I, and cycle II. A 19% increase in questioning abilities was observed from the pre-cycle to cycle I, followed by an impressive 33% increase from cycle I to cycle II. This progression illustrates that while students are making commendable strides in developing their questioning skills, they still benefit from targeted guidance from educators to refine the substance of their inquiries. Regarding collaboration skills, applying SEL resulted in a noteworthy 25% enhancement from the pre-cycle to cycle I and a further 42% improvement from cycle I to cycle II. These findings underscore a significant advancement in students' capacities for teamwork, responsibility, and constructive feedback within group dynamics. Overall, the insights gained from this study highlight the effectiveness of implementing social-emotional learning in enriching the educational experience and fostering collaboration and questioning skills among elementary school students.